Lipopolysaccharide structure modulates cationic biocide susceptibility and crystalline biofilm formation in Proteus mirabilis - Clarke, O. E.; Pelling, H.; Bennett, V.; Matsumoto, T.; Gregory, G. E.; Nzakizwanayo, J.; Slate, A. J.; Preston, A.; Laabei, M.; Bock, L. J.; Wand, M. E.; Ikebukuro, K.; et al. (Frontiers in Microbiology, 2023)
Chlorhexidine (CHD) is a cationic biocide used ubiquitously in healthcare settings. Proteus mirabilis, an important pathogen of the catheterised urinary tract, and isolates of this species are often described as "resistant" to CHD-containing products used for catheter infection control. To identify the mechanisms underlying reduced CHD susceptibility in P. mirabilis, we subjected the CHD tolerant clinical isolate RS47 to random transposon mutagenesis and screened for mutants with reduced CHD minimum inhibitory concentrations (MICs). One mutant recovered from these screens (designated RS47-2) exhibited ~ 8-fold reduction in CHD MIC. Complete genome sequencing of RS47-2 showed a single mini-Tn5 insert in the waaC gene involved in lipopolysaccharide (LPS) inner core biosynthesis. Phenotypic screening of RS47-2 revealed a significant increase in cell surface hydrophobicity and serum susceptibility compared to the wildtype, and confirmed defects in LPS production congruent with waaC inactivation. Disruption of waaC was also associated with increased susceptibility to a range of other cationic biocides but did not affect susceptibility to antibiotics tested. Complementation studies showed that repression of smvA efflux activity in RS47-2 further increased susceptibility to CHD and other cationic biocides, reducing CHD MICs to values comparable with the most CHD susceptible isolates characterised. The formation of crystalline biofilms and blockage of urethral catheters was also significantly attenuated in RS47-2. Taken together, these data show that aspects of LPS structure and upregulation of the smvA efflux system function in synergy to modulate susceptibility to CHD and other cationic biocides, and that LPS structure is also an important factor in P. mirabilis crystalline biofilm formation.